Sexual Body Size Dimorphism in Small Mammals: A Case Study from Lithuania - Linas Balčiauskas; Laima Balčiauskienė (Biology)
We assessed the sexual size dimorphism (SSD), analyzing standard morphometric traits in juveniles, subadults, and adults, of 14 species of voles, mice, and shrews in Lithuania on the basis of long-term surveys, updating information published 35 years ago and in the context of data from other countries. ANOVA, t-tests, and a 5% threshold were used in the analyses. Male-biased SSD was observed in Apodemus flavicollis and Alexandromys oeconomus, which was subject to Rensch’s rule, and in three other meadow vole species, with the strongest expression in adult individuals. Female-biased SSD was best expressed in Clethrionomys glareolus and was also identified in four mouse species, although patterns were less consistent across age groups. Shrews and the smallest mouse, Apodemus uralensis, exhibited monomorphic traits. The transition of dimorphism during postnatal development was observed in some species. We present an assessment of SSD in Microtus rossiaemeridionalis and Sicista betulina, the less common small mammals not analyzed in publications by other authors, and provide new baseline data for boreal mid-latitude small mammal species as a foundation for future studies on SSD and its adaptive significance under shifting ecological pressures or climate change.